Grounding the Prosperity Gospel: Sites of Wealth and Power in Ghana - Lauterbach, Karen; Bob-Milliar, George M. (The Pentecostal World, 2023)
The prosperity gospel, or the health and wealth gospel, is often characterized as a Pentecostal movement and theological principle that has its roots in the United States and that has dispersed globally with a significant imprint on African Pentecostalism. This chapter presents an overview of grounding the prosperity gospel is based on an analysis of the project of building a National Cathedral in Accra, Ghana. The project was launched by President Nana Akufo-Addo in March 2017 and was presented at the occasion of the celebration of Ghana's sixtieth anniversary as an independent nation. In 2021, a fundraising campaign was launched and as part of that the secretariat for the National Cathedral project released a “fundraising documentary video.” Elizabeth Sackey, Regional minister for Greater Accra, gave an address at the event and it was reported “that the corporate prayer of Christians was necessary for the ‘permission and blessings of Heaven’ for the success of the project”.
paid